Learning through explaining: A case study of students' perceptions of oral mathematical communication in a complex variable function course - Bill Chairy Rizki Bustaren; Encum Sumiaty; Yusuf Adhitya; Fitri Rahmawati; Jay Fie Paler Luzano (UNION : Jurnal Ilmiah Pendidikan Matematika, 2026)
Oral mathematical communication is an important aspect of mathematics learning, particularly in advanced courses that involve abstract and symbolic concepts.  However, previous studies have mainly examined whether explaining improves learning, while less is known about how students perceive where learning occurs during oral explanation in advanced mathematics. This study aims to explore students’ perceptions of oral mathematical communication in a Complex Variable Function course. A qualitative case study design was employed involving 14 mathematics education students who had participated in oral explanation activities during the course. Data were collected through open-ended questionnaires and analyzed using reflexive thematic analysis. The findings revealed three main themes: explaining to understand, learning happens before speaking, and understanding through support and interaction. Students perceived oral explanation not merely as a speaking activity but as a learning process that helped them reorganize ideas, deepen conceptual understanding, and identify gaps in their knowledge. The most meaningful learning experience was often reported during the preparation stage, when students reviewed materials, searched for additional resources, and structured their explanations. Students also emphasized the importance of representations, lecturer feedback, peer discussion, and technological resources in supporting their understanding. The study did not independently measure learning gains but the findings from student’s perceptions suggest that oral explanation activities should be designed as structured learning experiences that include preparation, representation, interaction, and feedback.